A flame retardant polycarbonate composition and its preparation method and application
By adding a specific amount of sulfonate flame retardant and talc powder to the polycarbonate, combined with the appropriate particle size and pH range, the flame retardant properties and mechanical properties of the polycarbonate flame retardant materials in the prior art are solved. The problem of this achieves the balance of high strength, 2.0mm 5VA flame retardant performance and environmental protection requirements.
Patent Information
- Application Number
- CN202311259893.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-09-27
AI Technical Summary
The existing polycarbonate flame retardant materials cannot meet the high-strength, 2.0mm 5VA flame retardant performance requirements, and there are problems of environmental protection requirements and insufficient mechanical performance.
By adding 0.01 to 0.1 parts of sulfonate flame retardant, 0.03 to 0.1 parts of anti-drip agent and 2 to 8 parts of talc powder to the polycarbonate, the specific talc powder particle size and pH range (4 -8 microns, 7.5-8.8) to promote the formation of carbon layers and enhance flame retardant properties, while controlling the content of sulfonate flame retardant within 1000ppm.
It has achieved a polycarbonate composition with excellent 2.0mm 5VA flame retardant properties and high mechanical strength under a low-content sulfonate system, meeting the use needs of the electronic and electrical appliance industry, while also having environmental protection advantages.
Smart Images

Figure BDA0004472530350000061 
Figure BDA0004472530350000062 
Figure BDA0004472530350000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flame retardant carbonates, and in particular relates to a flame retardant polycarbonate composition and a preparation method and application thereof. Background Art
[0002] Polycarbonate (PC) is an engineering plastic with excellent performance and good comprehensive properties, such as high mechanical strength, good impact resistance, dimensional stability, good heat resistance and good electrical insulation. Based on these excellent properties of PC, it is widely used in home appliances, digital products, IT products and other fields. With the application and development of PC products in various industries, certain requirements are also put forward for its flame retardant properties.
[0003] Sulfonate flame retardant is a highly efficient polycarbonate flame retardant. Its mechanism of action is that the thermal decomposition products of sulfonate in the early stage of combustion promote the Fris rearrangement of polycarbonate, induce the rapid formation of a dense carbon layer on the surface of the part, isolate oxygen and heat, and block the occurrence of combustion. The higher the amount of sulfonate flame retardant added, the better the flame retardant effect. However, the flame retardant has been regulated by REACH environmental protection, requiring the amount of material added to be controlled within 1000ppm. Therefore, the flame retardant level of polycarbonate in this flame retardant system is subject to certain limitations. The current mature flame retardant system technology level on the market can meet the flame retardant performance of 1.5mmV-0 and 3.0mm5VA types. With the trend of thin-walled electronic and electrical product parts, the flame retardant demand for materials has been raised to the flame retardant performance requirements of thin-walled 2.0mm5VA, but the existing flame retardant system is difficult to achieve this type of thin-walled 2.0mm5VA flame retardant requirements. The main failure is that the spline drips and ignites when the spline burns vertically, and perforation occurs when the square plate burns. In addition, although other flame retardant systems have been reported to achieve 2.0mm5VA, this will result in the material not meeting REACH or halogen-free environmental protection requirements, or the material may have poor mechanical properties or heat resistance, and cannot meet the material usage requirements of the electronics and electrical industry.
[0004] In short, in order to obtain high strength, 2.0mm 5VA flame retardant and meet REACH environmental protection control, the material needs to be further optimized and modified. Summary of the invention
[0005] In view of the problems that the polycarbonate flame retardant materials involved in the above-mentioned prior art do not meet environmental protection requirements and have poor flame retardancy and mechanical properties, the present invention will provide a flame retardant polycarbonate composition and a preparation method and application thereof.
[0006] To achieve the above purpose, the following technical solutions are specifically included:
[0007] A flame retardant polycarbonate composition comprises the following components in parts by weight:
[0008] 100 parts of polycarbonate, 0.01-0.1 parts of sulfonate flame retardant, 0.03-0.1 parts of anti-dripping agent, and 2-8 parts of talc; the melt index of the polycarbonate is 5.5-25g / 10min, wherein the melt index is tested according to ISO 1133-12011 standard, and the test conditions are 300°C and 1.2kg; the average particle size of the talc is 4-8 microns, and the pH value of the talc is 7.5-8.8.
[0009] The pH test method of talcum powder comprises the following steps: weighing 30g of talcum powder and putting it into a polytetrafluoroethylene beaker, pouring 100mL of deionized water, stirring magnetically at 80°C for 60min, stopping stirring, cooling to 25°C and filtering by suction, and testing the pH value of the filtrate with a pH meter, which is the pH value of the talcum powder.
[0010] The first step of the Fris rearrangement of polycarbonate flame retardant carbonization is degradation. Alkalinity can promote the degradation of polycarbonate. The alkalinity of talcum powder can advance the degradation step, making the rearrangement faster during the flame retardant test to form more and stronger carbon layers for flame retardancy. However, too high alkalinity of talcum powder will cause serious degradation of PC, significantly reduce the notched impact strength of the material, and because of the excessive degree of degradation, the melt strength of the material is too low, resulting in the failure effect of dripping ignition in the 5VA combustion test strip test; too low alkalinity of talcum powder will not catalyze the degradation of polycarbonate to a sufficient extent, and the flame retardant effect is not ideal.
[0011] The talc powder of the specific particle size and alkalinity range of the present invention has two functions. On the one hand, the appropriate alkalinity of the talc powder is used to catalyze the Fris rearrangement of PC to catalyze the formation of the carbon layer. On the other hand, the flaky structure of the talc powder plays an effect similar to "reinforced concrete" in the process of carbon layer formation. Enhancing the strength of the carbon layer is conducive to achieving flame retardant 5VA and avoiding the failure of the square plate to burn through. The larger the particle size of the talc powder, the stronger the enhancement effect and the easier it is to pass the 5VA test. Therefore, to a certain extent, the flame retardant performance is enhanced by increasing the particle size of the talc powder. However, if the particle size of the talc powder is too large, there will be more defects at the junction of the talc powder and the resin, and the notched impact strength of the material will be significantly reduced. If the particle size of the talc powder is too small, the reinforcing effect of the talc powder when participating in the carbon layer structure is insufficient, and it is not enough to form a solid carbon layer, resulting in poor flame retardant effect. Therefore, the particle size of the talc powder also needs to be selected in a suitable range.
[0012] The average particle size of talc can be 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8 microns, etc., as well as specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0013] As a preferred embodiment of the present invention, the talc powder has a flake structure.
[0014] As a preferred embodiment of the present invention, the mass percentage of the talc in the polycarbonate composition is 4%-7%.
[0015] As a preferred embodiment of the present invention, the pH value of the talc is 8.4-8.7.
[0016] The average particle size of talc is often measured using conventional methods. Specifically, the average particle size D50 of talc powder particles can be measured by laser diffraction, grid screening, etc. Commonly used equipment includes Malvern dry / wet laser particle size analyzer.
[0017] As a preferred embodiment of the present invention, the melt index of the polycarbonate is 6 to 19 g / 10 min, wherein the melt index is tested according to ISO 1133-1 2011 standard, and the test conditions are 300° C. and 1.2 kg.
[0018] Sulfonate flame retardants may include various organic sulfonate flame retardants, including organic sulfonates having at least one carbon atom. The organic sulfonate may be an alkali metal salt, such as a sodium salt, a potassium salt, a lithium salt or a cesium salt, or an alkaline earth metal salt, such as a magnesium salt, a calcium salt, a strontium salt or a barium salt, or may be a salt of a metal element such as iron, tin or zinc, an ammonia salt or an organic alkylamine salt.
[0019] The organic group of the organic sulfonate can be substituted by a halogen atom (such as fluorine, chlorine or bromine). Among the halogen atoms, fluorine is the most preferred, and the alkali metal salt or alkaline earth metal salt of the perfluoroalkyl sulfonic acid represented by the general formula (CnF2n+1SO3)mM is common, wherein n represents a natural number of 1 to 10, M represents lithium, sodium, potassium and cesium, or magnesium, calcium, strontium and barium, and m is equal to the valence 1 or 2 of M. More specifically, perfluoromethane sulfonate, perfluoroethane sulfonate, perfluoropropane sulfonate, perfluorobutane sulfonate, perfluorohexane sulfonate, perfluoroheptane sulfonate, perfluorooctane sulfonate, etc. can be used. Among them, potassium perfluorobutane sulfonate is particularly suitable.
[0020] Specifically, at least one of alkylsulfonates, benzenesulfonates, alkylbenzenesulfonates, diphenylsulfonates, naphthalenesulfonates, 2,5-dichlorobenzenesulfonates, 2,4,5-trichlorobenzenesulfonates, diphenylsulfone-3-sulfonates, diphenylsulfone-3,3′-disulfonates, naphthalenetrisulfonates, and fluorine-substituted products thereof can be used.
[0021] As a further preferred embodiment of the present invention, the weight portion of the sulfonate flame retardant is 0.05-0.1 parts.
[0022] As a preferred embodiment of the present invention, the weight content of the sulfonate flame retardant in the polycarbonate composition is not higher than 1000 ppm.
[0023] As a preferred embodiment of the present invention, the anti-dripping agent is polytetrafluoroethylene (PTFE).
[0024] A method for preparing a flame retardant polycarbonate composition comprises the following steps:
[0025] The method comprises the following steps: uniformly mixing polycarbonate, sulfonate flame retardant, talcum powder and anti-dripping agent, and then melting and extruding granulation to obtain the flame retardant polycarbonate composition.
[0026] As a preferred embodiment of the present invention, the extrusion temperature is 230-280°C.
[0027] As a preferred embodiment of the present invention, the extrusion temperature is 230-260°C.
[0028] The application of a flame retardant polycarbonate composition in electronic and electrical products can meet the requirements of electronic and electrical products for mechanical and flame retardant properties, and can be specifically applied to flame retardant plastic parts of audio, television, computer, camera and the like.
[0029] Compared with the prior art, the present invention has the following beneficial effects: the present invention can make the flame-retardant polycarbonate composition have excellent 2.0mm 5VA flame retardant performance by controlling the particle size and pH value range of talcum powder under a low-content sulfonate flame retardant system (10-1000ppm), while having the advantages of high mechanical strength and environmental protection, and is particularly suitable for electronic and electrical products. DETAILED DESCRIPTION
[0030] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0031] Talc pH Test:
[0032] Weigh 30 g of talcum powder into a polytetrafluoroethylene beaker, pour in 100 mL of deionized water, stir magnetically at 80°C for 60 min, stop stirring, cool to 25°C and filter with suction, and test the pH value of the filtrate with a pH meter.
[0033] Talc surface treatment:
[0034] Weigh 30 g of talc powder and put it into a polytetrafluoroethylene beaker, pour in 100 mL of glacial acetic acid, stir magnetically at room temperature for a certain period of time to react, then filter it with suction, and put the talc powder into a 60°C oven to dry for 60 minutes. By controlling the reaction time of talc powder in glacial acetic acid, the pH value of the surface of the treated talc powder can be adjusted.
[0035] Raw material information:
[0036] Polycarbonate 1#: PC 7030R, melt index 4.2g / 10min, Mitsubishi, Japan;
[0037] Polycarbonate 2#: PC WY-106BR, melt index 6g / 10min, Lihuayi;
[0038] Polycarbonate 3#: PC 2100, melt index 10g / 10min, Wanhua Chemical;
[0039] Polycarbonate 4#: PC 2220, melt index 19g / 10min, Wanhua Chemical;
[0040] Polycarbonate 5#: PC H-3000F, melt index 30g / 10min, Mitsubishi, Japan;
[0041] Polycarbonate 6#: PC S-3000VR, melt index 15g / 10min, Mitsubishi, Japan;
[0042] The test method for the polycarbonate melt index is as follows: in accordance with ISO 1133-1 2011 standard, the test conditions are 300°C / 1.2kg.
[0043] Sulfonate flame retardant: potassium perfluorobutane sulfonate SC4, Jiangxi Guohua Chemical;
[0044] Anti-dripping agent: polytetrafluoroethylene AD541, Changshu Zhenfu New Materials Co., Ltd.;
[0045] Talc 1: TY90-13C, average particle size D50 is 8.0 μm, pH value is 8.7, Dongguan Sanzhi New Materials Co., Ltd.
[0046] Talc 2: TY90-20-A, average particle size D50 is 8.5 μm, pH value is 8.7, Dongguan Sanzhi New Materials Co., Ltd.
[0047] Talc 3: HTP Ultra 5L, average particle size D50 is 0.65 μm, pH value is 8.5, Liaoning Aihai Yimi Mining Co., Ltd.
[0048] Talc 4: TYT-3000A, average particle size D50: 4.2 μm, pH value: 8.4, Guangzhou Tianyuan Chemical Co., Ltd.
[0049] Talc 5: FQ-5C, average particle size D50 is 5.12 μm, pH value is 9.2, Haicheng Yingluo Fuquan Stone Powder Factory, and talc 5 is subjected to the following talc surface treatment to prepare talc 5-1 to talc 5-4, and the average particle size D50 thereof remains unchanged, all being 5.12 μm:
[0050] Talc 5-1: treated with glacial acetic acid for 10 min, pH value is 8.7;
[0051] Talc 5-2: treated with glacial acetic acid for 30 min, pH value is 7.1;
[0052] Talc 5-3: treated with glacial acetic acid for 19 minutes, pH value is 7.5;
[0053] Talc 5-4: Treated with glacial acetic acid for 14 minutes, pH value is 8.4.
[0054] Flame retardant polycarbonate composition test method:
[0055] Izod notched impact strength: Prepare according to ISO 180 2019 standard A-type notch, take 5 standard specimens, use a 2.75J pendulum to test the energy required for the specimen to break, and calculate the specimen Izod notched impact strength value.
[0056] 5VA specimen test method: Prepare specimens according to UL 94 2016 standard, use a 125mm flame, use half the height of the flame to contact the specimen, flame the specimen for 5 seconds and then remove it for 5 seconds, for a total of 5 times, record the burning state and time of the specimen after the 5th flame application, and do not allow the specimen to drip or ignite the absorbent cotton below, and the burning time to exceed 60 seconds;
[0057] 5VA square plate test method, prepare the sample according to UL 94 standard, use 125mm flame, use half the height of the flame to contact the square plate, apply the flame to the square plate for 5s and then remove it for 5s, for a total of 5 times. The square plate is not allowed to be burned through during the 5 flame applications.
[0058] 2.0mm 5VA flame retardant performance requirements: The extinguishing time of the fifth specimen test shall not exceed 60s and no dripping shall ignite the absorbent cotton below. At the same time, the square plate shall not be burned through after 5 flame applications.
[0059] Examples 1-11 and Comparative Examples 1-8
[0060] Embodiment 1-11 and comparative example 1-8 A method for preparing a flame retardant polycarbonate composition comprises the following steps:
[0061] The polycarbonate resin, sulfonate flame retardant, talcum powder and anti-dripping agent are mixed evenly, and then granulated by a twin-screw melting and extrusion extruder. The temperature range of the screw melting and extrusion is 230-260° C., and the speed range is 30-80 rpm.
[0062] Table 1 (by weight)
[0063]
[0064] Table 2 (by weight)
[0065]
[0066]
[0067] It can be seen from the above embodiments that the notched impact strength of the flame retardant polycarbonate composition is ≥500 J / m, which meets the mechanical strength required for practical applications. The fifth extinguishing time of the 5VA sample test is 3-50s. The 5VA sample test does not drip and ignite the absorbent cotton below, and the 5VA square plate does not burn through, that is, it meets the 2.0mm 5VA flame retardant performance.
[0068] It can be seen from Examples 2-5, 8-9 and Comparative Example 3 that even if the pH value of talcum powder is in the range of 7.5-8.8, the average particle size is greater than 4-8 microns, resulting in more defects at the junction of talcum powder and resin, and the notched impact strength of the flame retardant polycarbonate composition drops sharply; It can be seen from Example 4 and Comparative Example 4 that the pH value is in the range of 7.5-8.8, but the average particle size is less than 4-8 microns, and the talcum powder does not enhance the strength of the carbon layer of the flame retardant polycarbonate composition (which helps to achieve flame retardant 5VA) to a small extent, resulting in unqualified flame retardancy.
[0069] It can be seen from Example 5 and Comparative Examples 5-6 that even if the average particle size of talc is in the range of 4-8 microns, when the pH value is less than the range of 7.5-8.8, the alkalinity is too low, the degree of catalytic degradation of polycarbonate is insufficient, and the flame retardant effect is not ideal; when the pH value of talc is greater than the range of 7.5-8.8, the alkalinity of talc is too high, which will cause serious degradation of PC, and the notched impact strength of the material will be significantly reduced. In addition, due to the excessive degree of degradation, the melt strength of the material is too low, resulting in a failure effect of dripping ignition in the 5VA combustion strip test.
[0070] It can be seen from Examples 2, 6-8 and Comparative Examples 7-8 that if the talc content is too little, the flame retardant properties of the flame retardant polycarbonate composition are poor; if the talc content is too much, the compatibility with polycarbonate is poor and the dispersion effect is poor, resulting in a significant decrease in its flame retardant properties and impact strength. When the weight proportion of talc is 2-7 parts, the impact strength is relatively ideal.
[0071] It can be seen from Examples 1-3, 11 and Comparative Examples 1-2 that the higher the polycarbonate melt index, the lower the molecular weight, the higher the content of reactive end groups, the more sensitive to the alkalinity of talc, and the polycarbonate in the composition is more easily degraded by the alkalinity of talc, so the flame retardancy deteriorates after the fluidity (melt index is too high), so the talc with a pH value of 7.5-8.8 of the present invention is too alkaline for the PC of Comparative Example 2, and the flame retardant effect cannot be achieved. Therefore, in the system of the present invention, it is necessary to simultaneously meet the melt index of a specific polycarbonate, the particle size of talc and the pH value range, so that the present invention can obtain a flame retardant polycarbonate composition with high mechanical strength, excellent flame retardancy and environmental protection requirements.
[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A flame retardant polycarbonate composition, It is characterized in that The composition comprises the following components in parts by weight: 100 parts of polycarbonate, 0.01-0.1 parts of sulfonate flame retardant, 0.03-0.1 parts of anti-dripping agent, and 2-8 parts of talc; the melt index of the polycarbonate is 5.5-25g / 10min, wherein the melt index is tested according to ISO 1133-12011 standard, and the test conditions are 300°C and 1.2kg; the average particle size of the talc is 4-8 microns, and the pH value of the talc is 7.5-8.
8.
2. The flame retardant polycarbonate composition according to claim 1, It is characterized in that The weight content of the sulfonate flame retardant in the polycarbonate composition is not higher than 1000 ppm.
3. The flame retardant polycarbonate composition according to claim 1, It is characterized in that The talc powder has a flaky structure; the mass percentage of the talc powder in the polycarbonate composition is 4%-7%.
4. The flame retardant polycarbonate composition according to claim 1, It is characterized in that The pH value of the talc is 8.4-8.
7.
5. The flame retardant polycarbonate composition according to claim 1, It is characterized in that The polycarbonate has a melt index of 6 to 15 g / 10 min.
6. The flame retardant polycarbonate composition according to claim 1, It is characterized in that The sulfonate flame retardant includes at least one of alkyl sulfonate, benzene sulfonate, alkylbenzene sulfonate, diphenyl sulfonate, naphthalene sulfonate, 2,5-dichlorobenzene sulfonate, 2,4,5-trichlorobenzene sulfonate, diphenyl sulfone-3-sulfonate, diphenyl sulfone-3,3'-disulfonate, naphthalene trisulfonate and fluorine-substituted products thereof.
7. The flame retardant polycarbonate composition according to claim 1, It is characterized in that The anti-drip agent is polytetrafluoroethylene.
8. A method for preparing the flame retardant polycarbonate composition according to any one of claims 1 to 7, It is characterized in that The method comprises the following steps: uniformly mixing polycarbonate, sulfonate flame retardant, talcum powder and anti-dripping agent, and then melting and extruding granulation to obtain the flame retardant polycarbonate composition.
9. Use of the flame retardant polycarbonate composition according to any one of claims 1 to 7 in electronic and electrical products.
Citation Information
Cited By
Silica micropowder-talcum powder composite synergistic flame retardant as well as preparation method and application thereof
CN122520980A
